Effect of organic matter and cation exchange capacity on the acidity of soils cultured with corn in two regions of Chiapas, Mexico - Cruz-Macías, Wel Olveín; Rodríguez-Larramendi, Luis Alfredo; Salas-Marina, Miguel Ángel; Hernández-García, Vidal; Campos-Saldaña, Rady Alejandra; Chávez-Hernández, Moisés Hussein; Gordillo-Curiel, Alder (REVISTA TERRA LATINOAMERICANA, 2020)
One third of the world’s soils are acidic, under these conditions many crops are affected, especially when aluminum concentrations reach toxic levels. In order to establish the relationships between acidity indicators and cation exchange capacity, and pH and organic matter content, 13 sites were selected in Frailesca and Valles Zoque regions. Five sub-samples were collected at a depth of 0.30 m, in order to form a homogeneous sample per experimental site. Determination of pH, interchangeable cations, cation exchange capacity, organic matter content, and aluminium (Al3+) and hydrogen (H+) saturation was performed. The saturation percentage of Al3+ was exponentially correlated with increases in CIC, pH and calcium (Ca2+) saturation %; however, in regard to organic matter, Al3+ saturation adjusted significantly to a second order polynomial model, indicating a maximum saturation at values of 4.14% of organic matter. The percentage of H+ saturation adjusted negatively to an exponential function, decreasing at organic matter values higher than 2%. It is concluded that in the soils of Frailesca region, there is an acidification process that could lead to toxic increases of aluminum for corn culture, especially at pH values lower than five.